Ferritin Levels as Indicators of Severity and Mortality in COVID-19 Patients from Tripoli, Libya - Samia A. Hassan; Rasha J. Aleqabi; Laila Faitory; Hanan G. Mady; Fatma Ben Rabha (Iraqi Journal of Industrial Research)
The rapid development of coronavirus disease nineteen (COVID-19) into a pandemic within months has posed significant risks, particularly for the elderly and individuals with underlying medical conditions. The primary driver of COVID-19 severity and mortality is the cytokine inflammatory storm. Elevated levels of ferritin, resulting from this storm and secondary hemophagocytic lymphohistiocytosis, have been observed in severe COVID-19 patients. The cytokine storm represents an uncontrolled and dysfunctional immune response within the pathogenic mechanism of COVID-19, leading to acute respiratory distress syndrome (ARDS) and systemic organ failure. Ferritin, an iron storage protein crucial for regulating cellular oxygen metabolism, shows a significant correlation with disease severity in COVID-19 patients.This study, conducted across three Libyan hospitals and two private laboratories from 2018 to 2022, targeted 500 cases to investigate ferritin's role in COVID‐19. Polymerase Chain Reaction (PCR) tests confirmed COVID-19 positivity. Ferritin levels were measured using a fully automatic device, revealing high levels in almost all positive cases, with some experiencing levels as high as 4532 ng/ml. Analysis of 209 negative COVID-19 cases before and after the pandemic showed consistently low or normal ferritin levels. Among the positive cases, 250 were admitted to the ICU, with a significant proportion experiencing elevated ferritin levels, and 82 ICU patients succumbed to the disease. Gender and age did not seem to influence ferritin elevation in COVID-19 cases. In conclusion, increased ferritin levels may indicate worsening COVID-19 cases and could be associated with disease severity and mortality.